Advancements in starch-based nanomaterials for functional delivery and food packaging: a comprehensive review and future directions - Siyuan Ma; Jiangling He; Qianqian Chen; Jiaojiao Zhou; Fang Xie; Jie Cai (Journal of Future Foods)
Starch-based nanomaterials have attracted global attention among researchers owing to their large specific surface areas (beneficial for increased nutrient loading) and abundant hydroxyl groups, distinguishing their physicochemical properties from traditional starch-based materials. This review comprehensively outlined the common types of starch-based nanomaterials and their construction methodologies, including acid and enzymatic hydrolysis, chemical precipitation, electrospinning, and ultrasonic crushing. The potential of these nanomaterials in the field of food applications is discussed. This review also detailed the construction approaches and applications of starch-based nanomaterials for encapsulating active substances in food nutrient and drug delivery. Owing to their large specific surface area, excellent stability, and pH responsiveness, starch-based nanomaterials facilitate improved loading rates and precise delivery of sensitive and easily decomposed active substances. In addition, incorporating bioactive substances into food packaging films, prepared from starch-based nanomaterials, can enhance antibacterial and antioxidant capabilities. Furthermore, the infusion of functional components with color responses into these films enables intelligent monitoring of changes in food quality during storage and transportation. Overall, this review provides contemporary insights into the functional delivery and food packaging applications of emerging microscale starch-based materials.